PHYTOCHEMICAL SCREENING OF DIFFERENT CRATAEGUS OXYACANTHA EXTRACTS - OLAH, Neli-Kinga; BURTESCU, Ramona Flavia; PETRESCU, Sorina; BRASOVAN, Andreea; CHIȘE, Elisabeta; COBZAC, Simona Codruța Aurora; HANGANU, Daniela (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Crataegus oxyacantha L., the hawthorn, is a well-known medicinal plant with cardiotonic effect. This paper presents a complex phytochemical screening of polyphenols profile, both qualitatively and quantitatively, in three different extracts obtained from fresh berries, flowers with leaves and young shoots. There were used spectral (UV-Vis) and chromatographic (TLC, HPLC) methods to evaluate the total flavonoids, total phenolic acids and qualitative polyphenols profile of the extracts. The antioxidant capacity was evaluated by DPPH, FRAP and NO radical inhibition methods, by UV-Vis spectrophotometry. The total flavonoid content expressed in rutoside ranges from 0.49 to 1.33 mg/ml, the total phenolic acids expressed in caffeic acid from 0.02 to 0.10 mg/ml, the most concentrated being the berries extract. In flowers with leaves extract can be identified and quantified a special flavonoid, the vitexine, 0.37 mg/ml. All three extracts present important antioxidant activity, both on ROS and RNS species. By FRAP method the berries extract was determined as most powerful, having also the best inhibition effect on NO radicals. The DPPH method indicates the special young shoots extract, used in gemmotherapy, as being the most powerful, with significant inhibiting effect on NO radicals. This indicates that the young shoots gemmotherapic extract is a good candidate for a powerful therapeutic tool.